Going Mobile: Language Learning With an iPod Touch in Intermediate French and German Classes. (17th September 2013) - Ducate, Lara; Lomicka, Lara
Abstract Mobile devices are becoming more and more pervasive in today's world for both personal use and educational purposes. Specific to the field of languages, mobile‐assisted language learning, derived from m‐learning and computer‐assisted language learning (CALL), differs from CALL in that it makes use of a personal portable device to enhance learning and give it the "anytime, anyplace" feature. Our study focused on both the learner and the mobile tool. We specifically investigated how students use mobile devices, specifically the iPod Touch, while noting differences in both personal and academic use. Using ecological constructivism as a theoretical framework, we examined the affordances of the mobile devices that encourage interaction with the target language and culture and explored a range of tasks using a mobile device.